Penguatan Pemahaman Kekerasan Berbasis Gender Online (KBGO) Bagi Guru-Guru SMA Muhammadiyah 3 Jakarta Selatan - Sri Mustika; Tellys Corliana; Andys Tiara; Yulmaida Amir (Warta LPM, 2023)
On the basis of the rapid increase in the use of digital access, especially for adolescents as the majority of internet users and concurrently with the KBGO case, "Strengthening Understanding of Online Gender-Based Violence for Teachers of SMA Muhammadiyah 3, South Jakarta" was held. Teachers were chosen as the target participants in this activity because teachers have an important role in this case. They need to educate their students about KBGO which has been happening more and more recently. The purpose of this strengthening is to provide an understanding of KBGO and as a trigger to create action in forming a means of handling and preventing KBGO in schools. PKM material in this strengthening includes Gender and Violence Against Women, The Role of Family Communication in Preventing KBGO, as well as the Impact of Violence on KBGO Victims and Ways to Overcome It. This activity went well and smoothly so that it was able to provide cognitive and affective effects on the participants who participated in this activity related to KBGO which threatens women including their students. Participants are also able to understand KBGO and ways to prevent KBGO and plan to create means to deal with and prevent KBGO for their students.